Saúde bucal do trabalhador e a assistência odontológica nas empresas - Cunha, Lucilene Sanches Cirilo da (2005)
The oral health attention should be directed to all age ranges and specific populations. It is easy to find preventive programs developed for children, pregnant women and elderly, yet few programs address the adult population. In an attempt to direct efforts to improve the oral health of workers, the present study was conducted to verify the existence and type of dental care provided by large companies at the central west region of the State of São Paulo (DIR X), besides verifying the oral health status of workers aged 35 to 44 years. The first stage comprised interview in the administrative sector of 17 companies. Then, oral health examinations were performed in 100 individuals of a company that agreed to participate in this stage. The results demonstrated that 85.71% of the companies surveyed offer dental care, predominantly by agreement with dental professionals in private practice associated to reimbursement of 50% of the value of treatment. The mean number of present teeth was 23.61 for males and 19.43 for females, being that nearly 70% presented 20 or more teeth in good conditions, approaching the WHO goal for the year 2000. It was concluded that the dental care provided to workers is offered as a benefit by most companies of DIR X. Programs directed to improvement of the oral health status of workers are required, to allow achievement of levels compatible with the goals established by the World Health Organization